L’évaluation du crédit marchand à Montréal dans la seconde moitié du dix-neuvième siècle - Lapalme, Alexandre (Journal of History, 2023)
This article examines one of the most prominent and powerful credit rating agencies in North America, the Mercantile Agency and its Montréal-based counterpart, Dun, Wiman & Co. The paper considers the context surrounding the first North American credit rating agencies, their managers’ profiles, the specific characteristics of the Montréal offices and, finally, the two primary methods of information transmission offered by the agency: the reference book and the credit report. I argue that issuing the reference book resulted in increasing access to credit for companies with high capitalization rates from creditors who possessed a subscription. Meanwhile, credit reports allow for greater flexibility in interpretation than a credit score. They thus offer additional leeway to debtor merchants who have little capitalization precisely because the creditor can interpret in various ways the content of the written evaluation. Foremost, the article provides an introduction to credit rating agencies as well as a general overview of the Montréal branch of the Mercantile Agency. Finally, the purpose of this research is to contribute to historiography by presenting an institution of credit regulation that has yet to receive much attention from the field of Canadian history.
Keywords: 19e siècle; 19th century; =CL; Montréal; agence d’évaluation de crédit; credit rating agencies; crédit marchand; economic regulation; economy; finance; histoire; history; mercantile credit; régulation économique; économie

Le libelle diffamatoire : une source aux potentialités multiples - Lapalme, Alexandre (Histoire engagée, 2018)
Keywords: =CL

Économie de la réputation commerciale. Une histoire du crédit marchand à Montréal au 19e siècle - Lapalme, Alexandre (Université de Montréal, 2022)
This thesis examines the credit records between 1847 and 1872 of the Montreal branch of the Mercantile Agency, among the most important credit bureaus in 19th century North America. The 19th century saw the acceleration of transatlantic trade. Montreal, located between Great Britain and the United States, was at the crossroads of the economic expansion. In this period, commonly referred to as the transition to capitalism, the legal, commercial and financial institutions of the metropolis were forced to adjust. In the financial sector, the state was compelled to adopt bankruptcy laws to lessen the negative effects of bad debts and to encourage and support the spread of commercial credit. However, because of limited accessibility, and the complexity and costs of the procedure, the laws were unable to fully guarantee the recovery of loans and were deemed unsatisfactory by the business community. The thesis claims that the emergence of credit agencies responded to the needs of the business community to address problems of information asymmetry. These agencies, like the Mercantile Agency, established a type of self-regulation of commercial credit. They provided information on risk to lenders. To a large extent, the information gathered represented the opinion of the Montreal merchant community. The credit offices of the Mercantile Agency used this information to generate rankings of the credit worthiness of merchants. The information was disseminated to the Agency’s network of subscribers. In this fashion, the Agency contributed to the construction of an economy of reputations. The research, which is inspired by contributions to the new history of capitalism, explores the effects of the construction of the economy of reputations on the relationship between lenders and borrowers. I find that the structure of the relationship favored creditor over debtors. The chapters of the thesis describe the role of reputation in the creditor-debtor relationship, the determinants adopted to measure credit worthiness, and the tensions and conflicts that emerged in the economy of reputations.
Keywords: 19e siècle; 19th century; =CL; Bankruptcy laws; Bureaux de crédit; Canadian history / Histoire du Canada (UMI : 0334); Capitalism; Capitalisme; Commerce; Commercial credit; Credit bureaus; Crédit marchand; Histoire; History; Lois sur les faillites; Montreal; Montréal; Reputation; Réputation

Économie morale et activité marchande dans le district de Montréal (1791-1815) : l’importance de la confiance et de la réputation - Lapalme, Alexandre (Université de Montréal, 2018)
Cette recherche analyse les concepts de confiance et de réputation par l’entremise de procès intentés pour libelle diffamatoire entre les années l791 et 1815 dans le district de Montréal. L’étude montre que la réputation, protégée juridiquement, est un régulateur de l’espace public. Elle contrôle les discours, les correspondances et tout autre écrit qu’un individu pourrait juger diffamants. En plus d’encadrer la liberté d’expression, la réputation structure le marché économique montréalais. Elle se présente comme l’un des moyens mis à la disposition des créditeurs comme des débiteurs pour créer la confiance. Inversement, sa flétrissure compromet l’échange. La réputation sera donc analysée dans ce mémoire comme l’une des formes de régulation sociale des rapports interindividuels au tournant du 19e siècle.
Keywords: =CL; Credit; Crédit; Espace public; Histoire; History; History - Canadian / Histoire - Canadienne (UMI : 0334); Moral economy; Public sphere; Reputation; Régulation sociale; Réputation; Social regulation; Économie morale